Behavior and Home Environment effect on the Air Germs Number in the Tuberculosis Patients Houses - Wanti, Wanti; Singga, Siprianus; Agustina, Agustina; Sila, Oktofianus; Irfan, Irfan (Window of Health : Jurnal Kesehatan, 2025)
The presence of germs, including Tuberculosis germs, in the house is greatly influenced by home environmental factors and TB sufferers behavior. This research aim is to determine the influence of home environmental factors and behavior on the number of air germs in the tuberculosis patients house in Kupang City. This observational research was conducted with purposive sampling in 21 homes with 21 TB patients from 86 patients from 2 Community Health Centers in Kupang City, NTT, Indonesia. The number of air germs with MPN coliform examination is measured based on laboratory examination. The independent variables are the number of people sleeping in the same room, type of walls, type of floor, ventilation conditions, wearing masks in the house, drying mattresses/pillows, place to expel phlegm, type of cooking fuel, smokers, sunlight entering the bedroom, sunlight entering the room. Going out and passive smoking. The data collected was then analyzed using multiple regression, and result in the equation: Number of Air germs = -203,614 + 59,538Ventilation Conditions + 86,333Drying MattressPillows + 63,841Smoking + 83,515Mthr Light to Room. The model shows that 61% of the number of air germs in the Tuberculosis patient's house is influenced by ventilation conditions, the habit of drying cases and pillows, the ability to smoke, and sunlight entering the rooms of Tuberculosis sufferers. This regression model is suitable for predicting the number of room air germs, where the fewer ventilation conditions, the germ number will increase, so the less frequently drying mattresses and pillows can also impact increasing the number of air germs in the homes of Tuberculosis sufferers. The number of room germs will also increase with smoking behavior and lack of direct sunlight in the bedroom.